Effect of intravenous immunoglobulin therapy on the prognosis of patients with severe fever with thrombocytopenia syndrome and neurological complications - Liu, Yun; Tong, Hanwen; He, Fei; Zhai, Yu; Wu, Chao; Wang, Jun; Jiang, Chenxiao (Frontiers in Immunology, 2023)
Background: Intravenous immunoglobulin (IVIG) has been reported to exert a beneficial effect on severe fever with thrombocytopenia syndrome (SFTS) patients with neurological complications. However, in clinical practice, the standard regime is unclear and there is a lack of evidence from large-scale studies. Methods: A single-center retrospective study was conducted to determine the influence of IVIG dosage and duration on SFTS patients with neurological complications. The primary outcome was 28-day mortality, and laboratory parameters before and after IVIG treatment were measured. Survival curves were generated using the Kaplan-Meier method and analyzed with the log-rank test according to the median IVIG dosage and IVIG duration. Besides, multivariate Cox regression analysis was performed to examine the association between the independent factors and the 28-day mortality in SFTS patients. Results: Overall, 36 patients (58.06%) survived, while 26 (41.9%) patients died. The median age of the included patients was 70 (55-75) years, and 46.8% (29/62) were male. A significantly higher clinical presentation of dizziness and headache was observed in the survival group. The IVIG duration in the survival group was longer than that in the death group (P < 0.05). Additionally, the IVIG dosage was higher in the survival group than in the death group, but there was not a statistically significant difference between the two groups (P = 0.066). The mediating effect of IVIG duration was verified through the relationship between IVIG dosage and prognosis using the Sobel test. Univariate analysis revealed that IVIG dosage (HR: 0.98; 95% CI: 0.97-1.00; P = 0.007) and IVIG duration (HR: 0.54; 95% CI: 0.41-0.72; P < 0.001) were significantly associated with risk of death. The multivariate analysis generated an adjusted HR value of 0.98 (95% CI: 0.96-1.00; P = 0.012) for IVIG dosage and 0.26 (95% CI: 0.09-0.78; P = 0.016) for dizziness and headache. Conclusions: Prolonged high-dose IVIG is beneficial to the 28-day prognosis in SFTS patients with neurological complications.